Effects of Malassezia yeasts on serum Th1 and Th2 cytokines in patients with guttate psoriasis. (18th April 2012) - Aydogan, Kenan; Tore, Okan; Akcaglar, Sevim; Oral, Barbaros; Ener, Beyza; Tunalı, Sukran; Saricaoglu, Hayriye
Abstract Background Systemic and focal infections caused by microorganisms have been known to induce or exacerbate psoriasis. Although the role of yeast species of the genus Malassezia in the pathogenesis of psoriasis is not fully understood, it is thought that these lipophilic yeasts may represent a triggering factor in the exacerbation of psoriatic lesions. Objectives This study investigated the effects of Malassezia yeasts on serum Th1 and Th2 cytokines in patients with guttate psoriasis (GP) in order to define their role in the pathogenesis of psoriasis. Methods Fifty patients with GP and 29 clinically healthy individuals were included in the study. All samples consisted of scales and scrapings taken from the scalps, trunks, and upper limbs of both psoriasis patients and healthy subjects. Psoriasis patients and healthy subjects were grouped according to their positivity or negativity for Malassezia yeasts as ascertained by direct microscopy and/or culture. An enzyme‐linked immunosorbent assay (ELISA) was used to measure serum levels of Th1 and Th2 cytokines in these groups. Results No significant differences in positivity for Malassezia yeasts were found between psoriatic skin and healthy skin in samples taken from different body sites. Serum interleukin‐13 (IL‐13) levels were significantly lower in the psoriasis group compared with the control group (P = 0.04). Levels of other cytokines did not differ significantly between the psoriasis and control groups. Mean levels of Th2 cytokines (IL‐4, IL‐10, IL‐13), but not of Th1 cytokines (IL‐2 and IFN‐γ), were significantly lower in psoriasis patients positive for Malassezia yeasts compared with those negative for Malassezia yeasts and control subjects (P = 0.04, P < 0.001 and P = 0.01, respectively). Conclusions The isolation of Malassezia yeasts from GP lesions does not necessarily mean that these species are pathogenic, but their downregulating effects on anti‐inflammatory Th2 cytokines may contribute to the occurrence of GP.